Pulmonary disease due to Mycobacterium kansasii in São Paulo, Brasil - Silva, Eny Aparecida Matheus da (1987)
The occurrence of 9 cases of human pulmonary infection due to Mycobacterium kansasii was disclosed in the ABCD region of Metropolitan São Paulo during the period 1984-1985. The patients showed clinical manifestations of chronic respiratory iIlness. The mycobacteria were isolated, identified and tested for drug sensitivity. These observations showed the limitations of the knowledge on mycobacteria other than M.tuberculosis. Because clinical, radiologic and histologic studies are as yet insufficient for the differentiation of pulmonary diseases due to various types of acid-fast organisms, bacteriological identification of each strain is required.